Colorimetric detection of mercury ions based on plasmonic nanoparticles - Du, Jianjun (2014)
The development of rapid, specific, cost-effective, and robust tools in monitoring Hg2+ levels in both environmental and biological samples is of utmost importance due to the severe mercury toxicity to humans. A number of techniques exist, but the colorimetric assay, which is reviewed herein, is shown to be a possible tool in monitoring the level of mercury. These assays allow transforming target sensing events into color changes, which have applicable potential for in-the-field application through naked-eye detection. Specifically, plasmonic nanoparticle-based colorimetric assay exhibits a much better propensity for identifying various targets in terms of sensitivity, solubility, and stability compared to commonly used organic chromophores. In this review, recent progress in the development of gold nanoparticle-based colorimetric assays for Hg2+ is summarized, with a particular emphasis on examples of functionalized gold nanoparticle systems with oligonucleotides, oligopeptides, and functional molecules. Besides highlighting the current design principle for plasmonic nanoparticle-based colorimetric probes, the discussions on challenges and the prospect of next-generation probes for in-the-field applications are also presented.